The mediating effect of financial performance on the relationship between social responsibility and ownership structure - Hayam Wahba; Khaled Elsayed (Future Business Journal, 2015)
Existing literature is inconclusive about the relationship between social responsibility and institutional investors as it assumes, implicitly, that this relationship is direct. An alternative perspective, that has received less attention in the literature, is that this relationship can be mediated by other contextual variables such as financial performance. Thus, this study is aiming to provide some empirical evidence on this issue that may help in explaining divergence in prior work. Panel data regression was performed on a sample that includes all firms that are listed in the Egyptian social responsibility index during the period from 2007 to 2010. The results demonstrate that better (or worse) financial performance, and rather social responsibility, is the lead for institutional investors when they make their investment decisions.
Keywords: 650; Corporate social responsibility; Egypt; Financial performance; Institutional investors; Panel data